2014
DOI: 10.1097/aog.0000000000000541
|View full text |Cite
|
Sign up to set email alerts
|

Management of Multiple Sclerosis During Pregnancy and the Reproductive Years

Abstract: Although there are many unmet research needs, the reviewed data support the conclusion that in the majority of cases, women with MS can safely choose to become pregnant, give birth, and breastfeed children. Clinical management should be individualized to optimize both the mother's reproductive outcomes and MS course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(65 citation statements)
references
References 147 publications
1
63
0
1
Order By: Relevance
“…In the best-worst scaling, one patient reported an additional attribute to be important: the effect of the DMD during pregnancy on the unborn child. Although it is generally recommended to discontinue DMD treatment before trying to conceive, treatment with certain DMDs can be continued in case of highly active MS [3236]. Moreover, during DMD treatment patients may become pregnant inadvertently.…”
Section: Discussionmentioning
confidence: 99%
“…In the best-worst scaling, one patient reported an additional attribute to be important: the effect of the DMD during pregnancy on the unborn child. Although it is generally recommended to discontinue DMD treatment before trying to conceive, treatment with certain DMDs can be continued in case of highly active MS [3236]. Moreover, during DMD treatment patients may become pregnant inadvertently.…”
Section: Discussionmentioning
confidence: 99%
“…MS is more prevalent among females, and the peak age of onset for women is during the childbearing years. 1,2 MS does not seem to significantly impair fertility although there is emerging data on decreased ovarian reserve and higher prevalence of thyroid autoimmunity in MS patients, possibly affecting fertility. 25 A chronic neurologic illness may also influence pregnancy intentions.…”
Section: Introductionmentioning
confidence: 98%
“…1,2 MS does not seem to significantly impair fertility although there is emerging data on decreased ovarian reserve and higher prevalence of thyroid autoimmunity in MS patients, possibly affecting fertility. 25 A chronic neurologic illness may also influence pregnancy intentions. Although some patients report having completed their families prior to MS diagnosis, one study found that among women with MS who did not become pregnant after diagnosis, nearly one-third cited MS-related concerns such as symptoms interfering with parenting, burdening their partner, and children inheriting MS. 6 Many women with MS use disease modifying therapies (DMTs).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations